From Burden to Blessing: Transforming the Meaning of Clinical Supervision - Sembiring, Desy Anita Karolina; Mangando, Widyaskara (JURNAL AL-TANZIM, 2026)
This study aims to explore how clinical supervision can be transformed from a bureaucratic burden into a reflective professional learning experience in schools. Clinical supervision, although designed to enhance teacher professionalism, is often perceived as evaluative and threatening, limiting reflective practice and instructional innovation. To address this, a phenomenological case study was conducted using in-depth interviews, observation, and document analysis. Data were analyzed using Miles and Huberman's model, including an iterative hermeneutic process of reduction, display, and interpretation. The findings revealed three main outcomes: first, teachers developed sustained professional reflectivity, critically assessing and improving their instructional practice; second, teacher identity and self-confidence were strengthened, fostering independent and bold pedagogical experimentation; and third, a professional learning community emerged, promoting collaborative reflection and culturally responsive practice. This study contributes theoretically by framing clinical supervision as a culturally reflective praxis and by providing strategies for integrating local cultural values into supervision. Future research should examine its longitudinal impact on teacher development and student outcomes.